A special prison regime (Rivista di Studi e Ricerche sulla criminalità organizzata, 2023)
The author offers a critical guide to the current debate of the 41-bis special detention regime, pointing out critical issues, urgencies and risks in the need to open a clear discussion on the special regime: on its numerical extension, on its too often unlimited duration, on the material conditions of detention, on the individual measures and on the scrupulous protection of the rights which pertain to the person and which constitute the indispensable fulcrum of a democratic system.
Keywords: special prison regime; article 41-bis; organized crime; prison; rights